The Mediating Role of Emotion Regulation in the Relationship Between Parent-Child Relationship Quality and Risky Behaviors in Adolescents - Jamali , Ali; Rafiepoor , Amin (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: Adolescence is a critical period in life. During adolescence, individuals experience new situations and, as a result, face various risks. The present study aims to determine the mediating role of emotion regulation in the relationship between the quality of the parent-child relationship and risky behaviors in adolescents. Methods and Materials: This study is descriptive-correlational in terms of data collection and structural equation modeling in nature. The study population includes all adolescents in Tehran city. Based on Morgan’s table, 222 individuals were selected as the sample size through a convenient sampling method and participated in the current study. Data were collected using the Parent-Child Relationship Assessment questionnaire, the Cognitive Emotion Regulation questionnaire, and the Adolescent Risk-Taking Scale. Data analysis was conducted using Pearson correlation analysis and path analysis in the AMOS and SPSS version 22 software. Findings: The results of the research showed that maladaptive emotion regulation is significantly positively correlated with risky behaviors in adolescents (P < 0.01). The quality of the parent-child relationship had a significant negative correlation with components of risky behaviors in adolescents (P < 0.01). Conclusion: Other findings of this research indicated that emotion regulation strategies play a mediating role in the relationship between the quality of the parent-child relationship and risky behaviors. Therefore, in adolescents, the quality of the parent-child relationship determines risky behaviors through emotion regulation strategies.